Verification of Interaction Between Cl− Erosion and Carbonation in Marine Concrete - Maohua Zhang; Lin Du; Ronghua Xu (Journal of Marine Science and Engineering)
Marine concrete frequently experiences performance degradation due to the combined effects of chloride ion (Cl−) erosion and carbonation. While many studies have examined the separate effects of Cl− erosion and carbonation, their combined impact on concrete is still debated. Investigating the interaction mechanisms between Cl− erosion and carbonation is crucial for improving the durability of concrete structures. This study utilizes a method where concrete specimens are immersed in artificial seawater with NaCl concentrations of 5%, 10%, and 15% prior to carbonation, with carbonation depth serving as a key indicator for analyzing the impact of Cl− erosion on carbonation. Both carbonation-treated and standard concrete specimens are immersed in 5% artificial seawater to evaluate the impact of carbonation on chloride erosion, with the free chloride content in the concrete serving as the assessment criterion. Scanning electron microscopy (SEM) is employed to examine the microstructure of the concrete, elucidating the interplay between Cl− erosion and carbonation. This study reveals that (1) Cl− erosion hinders concrete carbonation as NaCl crystals and Friedel’s salt in the pores limit CO2 penetration, with this effect intensifying at higher artificial seawater concentrations; (2) carbonation has a dual impact on Cl− erosion: in fully carbonated areas, carbonation products block pores and restrict Cl− diffusion, while at the interface between carbonated and non-carbonated zones, carbonation depletes Ca(OH)2, reducing Cl− binding capacity, increasing free Cl− content, and promoting Cl− diffusion.